Emerging therapeutic strategies for minimal change disease and focal and segmental glomerulosclerosis. (2nd November 2018) - Siligato, Rossella; Cernaro, Valeria; Nardi, Chiara; De Gregorio, Francesca; Gembillo, Guido; Costantino, Giuseppe; Conti, Giovanni; Buemi, Michele; Santoro, Domenico
ABSTRACT: Introduction : Minimal change disease (MCD) and Focal and segmental glomerulosclerosis (FSGS) are two of the major causes of nephrotic syndrome (NS) in children and adults. According to KDIGO (Kidney Disease: Improving Global Outcomes) guidelines, the treatment of adult primary MCD and FSGS should be based on immunosuppressants and antiproteinuric drugs. Recently, Rituximab, a humanized monoclonal antibody (mAb) has emerged as a potential treatment for steroid or calcineurin inhibitor-dependent patients; it has however demonstrated lower efficacy in those with nephrotic syndrome that is resistant to the above indicated drugs. Area covered : Analysis of ongoing and already completed clinical trials, retrieved from clinicaltrials.gov, clinicaltrialsregister.eu and PubMed involving new therapies for nephrotic syndrome secondary to MCD and FSGS. Expert opinion : The most promising drugs under investigation for MCD and FSGS are mAbs. We are hopeful that new therapeutic options to treat multi-drug resistant MCD and FSGS will emerge from currently ongoing studies. What appears certain is the difficulty in enrolling patients affected by orphan renal diseases and the selection of valid endpoints in clinical trials, such as kidney failure.